HYDROCEPHALUS IN PATIENTS WITH TUBERCULOUS MENINGITIS, ITS MANAGEMENT, AND OUTCOME - UDDIN , MM; JUMMANI , MM; ZULQARNAIN , D; BHATTI , T; SHAUKAT , S; ANSARI , AB; HALIM, SA; HAQ , MZU (Biological and Clinical Sciences Research Journal, 2024)
Hydrocephalus (HCP) is a common complication of tuberculous meningitis (TBM) that significantly impacts patient outcomes. Effective management strategies, including medical and surgical interventions, are essential to improve recovery and reduce disability and mortality rates. Objective: The objective of the present study is to determine the management and outcomes of HCP in patients with TBM. Methods: After the ethical approval from the institutional review board, this cross-sectional observational study was conducted at Shaheed Mohtarma Benazir Bhutto Institute of Trauma (SMBBIT), Karachi, from June 2022 to June 2024. Through non-probability consecutive sampling, 87 patients ages above 8 years, both genders, who are diagnosed and admitted for TBMH and who are classified in grades I to IV according to Modified Vellore grade were included in the present study. Results: Modified Vellore grading classified patients into Grade I (26%), Grade II (31%), Grade III (28%), and Grade IV (14%). Medical management included anti-tuberculous therapy (ATT) in all patients. Surgical intervention, such as ventriculoperitoneal shunting, was performed in 25% of cases, while 75% were managed non-surgically. At 12 months, 55% of participants showed good recovery, 22% had moderate disability, and 17% had severe disability, with a mortality rate of 6%. Stratification by age revealed significantly better outcomes in individuals under 50 years (p=0.02), with good recovery observed in 31 younger patients compared to 17 older ones. Conclusion: Male gender, younger age at onset, and better early treatment correlated with better recovery indicating that early diagnosis and appropriate therapy are crucial.